2004
DOI: 10.1677/joe.0.1800097
|View full text |Cite
|
Sign up to set email alerts
|

Role of putative membrane receptors in the effect of androgens on human vascular cell growth

Abstract: We have reported previously that dihydrotestosterone (DHT) induces a biphasic effect on DNA synthesis in human vascular smooth muscle cells (VSMC), i.e. stimulation at low concentrations and inhibition at high concentrations. In contrast, DHT dose-dependently stimulated [ 3 H]thymidine incorporation in a human endothelial cell line (ECV304). Additionally, DHT increased the specific activity of creatine kinase (CK) in both vascular cell types. In the present study, we have determined whether some of these effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
25
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 21 publications
7
25
3
Order By: Relevance
“…Although possibly not a phenomenon general in all human organs, this concept has been validated in other human endothelial cell models (92,93). A recent study in primary cultures of human aortic endothelial cells showed that AR activation led to moderate (a less than 2-fold increase) upregulation of VEGF-A, cyclin A, and cyclin D1 mRNA expression measured by real-time PCR; the latter two factors are involved in cell cycle progression (9).…”
Section: Androgen Action On Endothelium Of the Prostate And Prostate mentioning
confidence: 95%
“…Although possibly not a phenomenon general in all human organs, this concept has been validated in other human endothelial cell models (92,93). A recent study in primary cultures of human aortic endothelial cells showed that AR activation led to moderate (a less than 2-fold increase) upregulation of VEGF-A, cyclin A, and cyclin D1 mRNA expression measured by real-time PCR; the latter two factors are involved in cell cycle progression (9).…”
Section: Androgen Action On Endothelium Of the Prostate And Prostate mentioning
confidence: 95%
“…Hanke et al 113 reported, using an ex vivo organ culture system, that testosterone at 10-100 ng ml -1 significantly inhibited neointima formation in association with increased expression of AR in endothelium-denuded rabbit aortic rings after 21 days of incubation. Somjen et al 114 demonstrated the dose-dependent inhibitory effects of dihydrotestosterone and membrane-impermeable testosterone on DNA synthesis in cultured VSMCs derived from the human umbilical artery, suggesting a role for membrane AR. The above-mentioned study by Tharp et al 94 showed that the expressions of protein kinase C delta and p27 (kip1) were increased in coronary artery sections of testosterone-treated swine.…”
Section: Effects Of Testosterone On Ecsmentioning
confidence: 99%
“…Recent studies established the expression of functional membrane androgen receptors (mARs) inducing rapid nongenomic androgen actions in tumors, including prostate (1,2), breast (3,4) and colon (5) as well as in other cell types such as macrophages and T cells (6,7), C6 (8) and vascular smooth muscle cells (9). The exact molecular identity of mAR remains unknown.…”
Section: Introductionmentioning
confidence: 99%